Hydraulic reconstruction of catastrophic drainage from the Late Glacial, Lake Fraser, British Columbia, Canada - Sean M. Loeffler; John J. Clague; Brendan G. N. Miller; Sophie L. Norris (Journal of Quaternary Science, 2026)
Glacial Lake Fraser, which formed in British Columbia against the retreating Cordilleran Ice Sheet, stored ~520 km 3 of water before its near‐total drainage into the Salish Sea during an outburst flood event. Despite the impact of the outburst flood on sediment transport and landscape evolution in the Fraser River valley, its peak discharge and drainage duration are not well constrained. Here, multiple numerical modelling techniques are used to provide insight into the characteristics of the outburst flood. Boulder fields and giant gravel bars that provide evidence of water depth and flow dynamics are used to calibrate a step‐backwater model of peak discharge. This numerical estimate of peak discharge is compared with several ice‐dam failure scenarios, involving different parameters for the failure mechanism, duration and size, simulated using the HEC‐RAS dam‐breach model. The glacial Lake Fraser outburst flood had a peak discharge of at least 500 000–800 000 m 3 s −1 , and incision of the ice dam was likely relatively gradual, meaning that the lake drained over the course of several weeks. These findings improve our understanding of flood dynamics and enable more detailed estimations of the regional impacts of this event.